Team Effectiveness in The Workplace: Predictive Roles Of Self-Esteem And Perceived Social Support Among Civil Servants - Oguegbe, Tochukwu Matthew (Practicum Psychologia, 2024)
This research explored team effectiveness among civil servants: predictive roles of perceived social support and self-esteem. One hundred and eighty-seven (187) civil servants (one hundred and six females and eighty-one males), whose age ranged between 22 and 63 years, with a mean age of 41.12, standard deviation of 12.45, and were randomly selected, participated in the study. Multidimensional scale for perceived social support (MSPSS), Rosenberg self-esteem scale and the Team Effectiveness Questionnaire (TEQ) assisted in the data collection. The study made use of predictive design and multiple linear regression in testing the two hypotheses postulated. Hypothesis one which stated that perceived social support will significantly predict team effectiveness, was upheld, t = -3.184, p <.05. Hypothesis two which stated that self-esteem will significantly predict team effectiveness, was also affirmed, t = 2.037, p <.05. In line with this finding, it was recommended that for organisations to ensure a mutually beneficial relationship between the employer and employee as well as among the employees, policies that take psychological perspective to life should be enacted in all workplaces while ensuring that the public is sensitized on matters concerning mental wellbeing.